Factors Affecting Employee Good Organizational Behavior Thai Sugar Industry Co., Ltd. - Phetpankan, Saowaluk; Phonghanyudh, Surasaek; Poopatanapong, Kaewta (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The research about factors affecting employee good organization behavior of Thai Sugar Industry Co., Ltd. have an objectives for 1) Study the personal factors that affecting employee good organizational behavior of Thai Sugar Industry Co., Ltd. 2) Study the influence of the environment that affecting employee good organizational behavior of Thai Sugar Industry Co., Ltd.. The researcher use quantitative research to research the employee of Thai Sugar Industry Co., Ltd. that have 950 employee. Researcher use Krejcie and Morgan to find the sample population , 282 samples were available by using stratified random sampling. The equipment that used in the research are questionnaire that researcher created. Analyzed data by Frequency , Percentage , Mean , Standard Deviation , t-Test , One-way ANOVA and Multiple Regression. The result of this research found that 1) the employee good organization behavior of Thai Sugar Industry Co., Ltd. were statistically significant differences followed by the factors of the Status , Working Position and Duration of employment. 2)The influence of the environment that affecting employee good organizational behavior of Thai Sugar Industry Co., Ltd. consist of Supervision (β = 0.41) , Welfare or other benefits (β = 0.31) The Stability and Security (β = 0.14) and wage (β = 0.11) respectively. The accuracy in predicting is equal to 47 percent. Article history : Accepted 14 September 2017 SIMILARITY INDEX = 5.50